2017
DOI: 10.1108/jgm-05-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Job resources and demands for expatriate academics

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…On rules of thumb, job stressors/demands would contribute to employees' health impairment process (i.e., strain and burnout) 2014;. In line with this principle, the majority of results in the higher education realm assert the negative influence of high job demands on academic's well-being (Bell et al, 2012;Boyd et al, 2011;Han et al, 2020;Jonasson et al, 2017;Kinman and Jones, 2008). In the Malaysian context, examinations within RUs claimed that several jobs demands increase academics exhaustion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On rules of thumb, job stressors/demands would contribute to employees' health impairment process (i.e., strain and burnout) 2014;. In line with this principle, the majority of results in the higher education realm assert the negative influence of high job demands on academic's well-being (Bell et al, 2012;Boyd et al, 2011;Han et al, 2020;Jonasson et al, 2017;Kinman and Jones, 2008). In the Malaysian context, examinations within RUs claimed that several jobs demands increase academics exhaustion.…”
Section: Resultsmentioning
confidence: 99%
“…Job demands, whether from an individual or group level, influence employees' well-being and performance. While the optimum level of requests would associate with performance improvement and high productivity (Dollard et al, 2000;Tadić et al, 2015;Ventura et al, 2015), obstruct demands lead to academics' health impairment process (e.g., psychological strain/burnout), and negatively affect the universities' productivity (Biron et al, 2008;Idris and Dollard, 2011;Han et al, 2020;Jonasson et al, 2017). However, investigations on the psychological state of academics at RUs are still not satisfactory (Ismail and Noor, 2016;Lina, 2014;Makhbul and Khairuddin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We identified expatriate academics via university webpages. This approach is commonly used in the majority of surveys on expatriate academics that we know of (e.g., Davies et al, 2015; Jonasson et al, 2017; Richardson & Wong, 2018; Maharjan et al, forthcoming). Participants were recruited for this study by first identifying names at university webpages that appeared to originate from outside the given country.…”
Section: Methodsmentioning
confidence: 99%
“…Previous domestic studies (e.g., Bakker et al, 2007, 2010; Nahrgang et al, 2011; Zhang et al, 2020) found a fully mediated relationship between job resources and job satisfaction in which employees’ SWB act as the core mediator. Expatriate research has also showed that local and organizational support are effective in increasing expatriates’ cross-cultural adjustment (Bhaskar-Shrinivas et al, 2005; Hechanova et al, 2003), work well-being (Ballesteros-Leiva et al, 2017; De Paul & Bikos, 2015; Stroppa & Spieß, 2011), and job satisfaction (Jonasson et al, 2017). We, therefore, presume the mediation of SWB holds true in the international context, so we posit that expatriates’ subjective well-being mediates the relationship between expatriates’ interaction adjustment and job satisfaction:…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%